Metabolic control analysis using glycolytic inhibitor titrations in the MCF-7 breast cancer cell line - Hollocks, Stephanie Anne (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.